Discontinuation of Tyrosine Kinase Inhibitors in Chronic Myeloid Leukemia With Losing Major Molecular Response as a Definition for Molecular Relapse: A Systematic Review and Meta-Analysis - Chen, Kang-kang; Du, Tai-feng; Xiong, Pei-sheng; Fan, Guan-hua; Yang, Wei (Frontiers in Oncology, 2019)
Background: A new goal in treatment of chronic myeloid leukemia (CML) in patients with stable deep molecular response (DMR) is maintaining durable treatment-free remission (TFR) after discontinuing tyrosine kinase inhibitor (TKI) treatment. Methods: We conducted a systematic review and meta-analysis focusing on the efficacy and safety of TKI discontinuation but also exploring the factors contributing to successful TFR. Results: The search yielded 10 trials including 1601 patients. For patients who discontinued TKIs, the estimated weighted mean incidence of major molecular relapse was 16% (95%CI: 11-21), 34% (95%CI: 29-38), 39% (95%CI: 35-43) and 41% (95%CI: 36-47) at 3, 6, 12 and 24 months, respectively. Of these, 39%, 82% and 95% of molecular losses occurred within the first 3, 6 and 12 months. In safety analysis, among patients without TFR, 98% (95% CI: 96-100) were sensitive to TKI retreatment. No new safety issues were identified except TKI withdrawal syndrome, which appeared during the early TFR phase, with a weighted mean incidence of 27% (95%CI: 19-35). Our subgroup analysis suggested better TFR associated with interferon therapy (P=0.007), depth of molecular response (P=0.018) and duration of DMR (P<0.001). Conclusions: TFR as an extension of an approach to optimize management of CML is clinically feasible in approximately 59% of patients with sufficient TKI response. In the remaining 41% of patients with molecular relapse, discontinuing TKIs had no negative impact on clinical outcomes. Given the high heterogeneity among studies, the role of these predictors for successful TFR still requires further investigation.